The Relationship between Learning Strategies and Children's Learning Interest in TPQ Aisyiyah, Bagan Hulu Sub-District, Bangko District, Rokan Hilir Riau Regency - Medi Yasti; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The research of the study was the lack of interest in children's learning in TPQ Aisyiyah, Bagan Hulu Village, Bangko District, Rokan Hilir Regency, Riau Regency. This is presumably due to poor learning strategies. was purpose to see: 1) Description of children's interest in TPQ Aisyiyah, 2) Description of teaching strategies applied by educators in teaching at TPQ Aisyiyah 3) Understanding the relationship between teaching strategies and student interest in learning at TPQ Aisyiyah. using a quantitative approach, with the type of correlation. The study population was the research participants in TPQ Aisyiyah, which amounted to 37 people, the sampling technique used was Stratified Random Sampling and taken 50%, namely 19 people. Questionnaire data collection techniques with tools in the form of a list of statements. The data analysis formula and Rank Order for technique uses the percentage. The results found study : 1) The learning strategy at TPQ Aisyiyah was not good; 2) Children's interest in learning at TPQ Aisyiyah is low; 3) There is a significant relationship between teaching strategies and children's interest in learning at TPQ Aisyiyah. It is hoped that the managers of TPQ institutions can use teaching strategies that are in accordance with the learning needs of children to support more effective teaching activities.